2020
DOI: 10.1093/cercor/bhz221
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Axon Density, Myelination, and Fractional Anisotropy in the Human Corpus Callosum

Abstract: The corpus callosum serves the functional integration and interaction between the two hemispheres. Many studies investigate callosal microstructure via diffusion tensor imaging (DTI) fractional anisotropy (FA) in geometrically parcellated segments. However, FA is influenced by several different microstructural properties such as myelination and axon density, hindering a neurobiological interpretation. This study explores the relationship between FA and more specific measures of microstructure within the corpus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 100 publications
7
65
0
Order By: Relevance
“…Multi-shell diffusion-weighted data were pre-processed using a custom in-house pipeline comprising tools from both the FSL ( Andersson et al., 2003 ; Andersson and Sotiropoulos, 2016 ) and MRTrix ( Veraart et al., 2016 ; Vos et al., 2017 ) software packages and in-house software. Specifically, AP- and PA-encoded images were separately denoised (MRTrix dwidenoise, Veraart et al., 2016 ) and drift corrected ( Vos et al., 2017 ), then merged (with incorporated EPI, susceptibility and motion correction; FSL topup ( Andersson et al., 2003 ) and eddy ( Andersson et al., 2016 )) corrected for gradient non-linearity distortions ( Glasser et al., 2013 ) with spatio-temporal b-value/vector tracking ( Rudrapatna et al., 2018 ), and finally corrected for Gibbs ringing artefacts (MRTrix mrdegibbs, Kellner et al., 2016 ). Subsequent processing involved computation of: (i) free-water corrected fractional anisotropy (FA), mean diffusivity (MD) and radial diffusivity (RD) maps ( Hoy et al., 2014 ) from diffusion tensor MRI using the b = 1000 s/mm 2 shell (linear least squares estimation with outlier rejection, Chang et al., 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Multi-shell diffusion-weighted data were pre-processed using a custom in-house pipeline comprising tools from both the FSL ( Andersson et al., 2003 ; Andersson and Sotiropoulos, 2016 ) and MRTrix ( Veraart et al., 2016 ; Vos et al., 2017 ) software packages and in-house software. Specifically, AP- and PA-encoded images were separately denoised (MRTrix dwidenoise, Veraart et al., 2016 ) and drift corrected ( Vos et al., 2017 ), then merged (with incorporated EPI, susceptibility and motion correction; FSL topup ( Andersson et al., 2003 ) and eddy ( Andersson et al., 2016 )) corrected for gradient non-linearity distortions ( Glasser et al., 2013 ) with spatio-temporal b-value/vector tracking ( Rudrapatna et al., 2018 ), and finally corrected for Gibbs ringing artefacts (MRTrix mrdegibbs, Kellner et al., 2016 ). Subsequent processing involved computation of: (i) free-water corrected fractional anisotropy (FA), mean diffusivity (MD) and radial diffusivity (RD) maps ( Hoy et al., 2014 ) from diffusion tensor MRI using the b = 1000 s/mm 2 shell (linear least squares estimation with outlier rejection, Chang et al., 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…1 Compression of peripheral nerves leads to distortion of the axonal architecture, demyelination with or without poor remyelination, loss of the intrinsic vasculature and ultimately, brosis of the perineurial and epineurial connective tissue. 2,3 Diffusion tensor imaging (DTI) characterises tissue microstructure and generates reproducible [4][5][6][7] proxy measures of nerve 'health' which are sensitive to myelination, axon diameter, bre density and organisation [8][9][10] (Figure 1). DTI typically generates the following metrics: fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has long been suggested that inter-individual differences in callosal morphology are related to differences in functional hemispheric asymmetries (Galaburda, Rosen, & Sherman, 1990;Ringo, Doty, Demeter, & Simard, 1994;Witelson & Nowakowski, 1991). Recent neuroimaging studies in general support this notion as they have shown an association between measures of structural corpus callosum connectivity and the distribution of neuronal processing between the hemispheres (e.g., Friedrich et al, 2020;Haberling, Badzakova-Trajkov, & Corballis, 2011;Josse, Seghier, Kherif, & Price, 2008;Karolis, Corbetta, & De Schotten, 2019;Labache et al, 2020;Moffat, Hampson, & Lee, 1998;Westerhausen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%